International Terrorism in the Age of Information and Communication Technology - Usman, Ibrahim Ali; Tamunotonye Felix Owubokiri (Universitas Medan Area, 2023)
This research delves into the profound impact of Information and Communication Technology (ICT) on the globalization of terrorism. The central hypothesis posits that the evolution of ICT has facilitated the spread of terrorist operations across a truly global network. Leveraging Internet technology, individuals can now communicate across borders with ease, privacy, and unprecedented reach. This study specifically explores how terrorist acts are increasingly justified through ICT, examining the threats posed to international peace and security by the utilization of cutting-edge social media platforms such as WhatsApp, Facebook, Instagram, YouTube, and Twitter by groups like ISIS. Employing a historical-descriptive approach, the author gathered data from reliable secondary sources, encompassing both public and unpublished records. The findings reveal that certain terrorist organizations, notably ISIS, capitalize on the growing accessibility of ICT, particularly via social media, to enhance communication, recruit members, radicalize individuals, and orchestrate coordinated operations. The study emphasizes the necessity of comprehending the role of social media in terrorist recruitment and radicalization. Understanding the motivations behind an individual's radicalization and affiliation with terrorist groups is crucial for effective counterterrorism measures. The study concludes with recommendations, emphasizing the importance of investing in scientific discovery and economic growth areas less susceptible to terrorist exploitation.